Analisis Risiko dan Bahaya Kecelakaan Kerja di TPA Karangdiyeng Kabupaten Mojokerto - Uci Fida Fitriani; Naniek Ratni JAR (Jurnal Serambi Engineering, 2024)
Landfill or TPA (Tempat Pembuangan Akhir) is a place for dumping waste from human activities that reaches the final stage in waste management. Landfill have dangers and risks of accidents for workers who come into direct contact with waste, resulting in a risk of infection, injury and disorders. The focus of this research is to recognize probable hazards and analyze the factors that cause risks to workers at the Karangdiyeng TPA. This research uses observation analysis with the HIRARC (Hazard Identification Risk Assessment and Risk Control) and FMEA (Failure Mode And Effect Analysis) methods. The results of the research show that the risks of work accidents at Karangdiyeng TPA are in the low risk category with risk control using administrative control. One effort that can be made to minimize danger and risk is by planning Occupational Health and Safety (K3) at the landfill. K3 planning at TPA includes identification of hazards and risks, efforts to control hazards and risks, and K3 planning projections.